Korelasi Status Gizi Dengan Kejadian Stunting Pada Balita - AF, Swaidatul Masluhiya; Soares, Isabel Fatima (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Stunting is when a child grows slowly and is not as tall as the average child, caused by malnutrition for a long time (chronic nutritional problems). East Nusa Tenggara (NTT) is the province with the highest stunting rate in Indonesia in 2021, with a prevalence of 37.8%. There are 8 out of 10 toddlers in the category of malnutrition status with a value of -3 to -2 (BB/TB). This study aimed to determine the correlation between the nutritional status of toddlers and the incidence of stunting at Posyandu Sabulmil, Lakmaras, South Lamaknen District, Belu Regency, NTT. The study used correlation with the cross-sectional approach. The population in this study was 45 toddlers aged 2-4 years old, with 40 respondents as the sample chosen by the Simple Random Sampling technique with observation sheets and MCH books. The data were analyzed using the Chi-Square test. The results proved that most (62.5%) respondents had poor nutritional status, and the majority (55.0%) were stunted (short). The Chi-Square test shows that there is a correlation between the nutritional status of toddlers and the incidence of stunting at Posyandu Sabulmil, Lakmaras, South Lamaknen District, Belu Regency, NTT with p-value = (0.000) (0.05). The impact of not fulfilling nutritional intake is the main factor in the occurrence of malnutrition, so toddlers are prone to stunting. Malnutrition in toddlers causes them to get sick quickly and grow up not maximumly or have short body postures. Future researchers must provide counseling about a balanced nutritional intake for toddlers and counsel about "What's on my plate?" to mothers.